Efeito da radiação uv-vis e infravermelho no perfil metabolômico de compostos orgânicos voláteis de Glycine max - Martinez, Jesus David Sierra (2023)
Despite significant advances in means of production and agricultural controls, insects are still humans' main competitors for food. As a result of breeding programs for productivity gains, among other characteristics, most cultivars currently available do not present efficient mechanisms of resistance against insect pests. In this way, the comparative metabolomics study between wild genotypes and cultivars can recover fundamental information on mechanisms of constitutive and induced resistances associating these results to genes, proteins, and secondary metabolites of plant defense, opening a field of research for the development of products and sustainable practices of pest control. Thus, the main objective of this project was to evaluate the effect of UV-Vis radiation on the metabolomic profile of volatile organic compounds from Glycine max (L.) Merr. seeking to understand how environmental factors modify and stimulate their metabolism. In addition, we also seek the recognition of defense mechanisms that can be stimulated and used to control insect pests. The HS/GC-MS analyses detected 16 volatile compounds, mostly aldehydes, alcohols, Furan derivatives, and hydrocarbons, including some with recognized chemoprotective activity against light radiation such as Linalool, and related to the direct and indirect defense of the plant against herbivores. The wild (PI407270), conventional (BRS-284,) andtransgenic(RR2PRO) cultivars influence the choice of food for S. frugiperda before any irradiation treatment is applied, with the wild cultivar being the greatest deterrent, especially when it receives broad-spectrum irradiation. Hexanal; (E)-2-hexenal; n-hexano; 2-ethyl-furano and 1-octen-3-ol are the main VOCs that respond to UV-Vis-infrared irradiation treatments, serving as markers of the response to the abiotic stimulus and the presence of compounds such as n-hexano coincides withhigh rates of deterrence of S. frugiperda.